2008
DOI: 10.1016/j.clnu.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to a long term (4weeks) arginine- and precursor (glutamate, proline and aspartate)-free diet

Abstract: SummaryBackground & aims-It is not known whether arginine homeostasis is negatively affected by a "long term" dietary restriction of arginine and its major precursors in healthy adults. To assess the effects of a 4-week arginine-and precursor-free dietary intake on the regulatory mechanisms of arginine homeostasis in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Arginine is synthesized in the kidney from intestinal citrulline derived from glutamine, but it is considered to be a conditionally indispensable AA in severely stressed patients (46). Recent evidence in healthy adults fed a diet free of both arginine and precursors of arginine for 4 wk shows that arginine is a nutritionally dispensable AA; however, the functional requirement for arginine is unknown (42). Consistent with minimal arginine in GMP, plasma arginine concentrations were significantly lower with ingestion of the GMP compared with the AA diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine is synthesized in the kidney from intestinal citrulline derived from glutamine, but it is considered to be a conditionally indispensable AA in severely stressed patients (46). Recent evidence in healthy adults fed a diet free of both arginine and precursors of arginine for 4 wk shows that arginine is a nutritionally dispensable AA; however, the functional requirement for arginine is unknown (42). Consistent with minimal arginine in GMP, plasma arginine concentrations were significantly lower with ingestion of the GMP compared with the AA diet.…”
mentioning
confidence: 99%
“…Urea is produced linearly in response to plasma AA concentrations, and control of nitrogen balance is primarily regulated by urea production (41). BUN, as a measure of hepatic utilization of AAs for urea synthesis, would be expected to remain lower with slower splanchnic AA release (40,42). Thus, a slower, more gradual and sustained elevation in plasma AA concentration with an intact protein source (33), in conjunction with a lower BUN concentration, suggests that fewer AAs are degraded for urea production and instead are retained for protein synthesis when GMP is substituted for synthetic AAs as the primary protein source.…”
mentioning
confidence: 99%
“…Because we consider it unethical to maintain neonates for long periods on a deficient diet, we did not test adaptation longer than 6 d and consequently did not resolve the question of whether more than 6 d has an additional effect on the tracer oxidation. Furthermore, in adult humans fed a 4-wk arginine-free diet, the decrease in oxidation was similar to a 1-wk restriction alone (15,18).…”
Section: Articlesmentioning
confidence: 76%
“…This would imply that when the adaptation to the enrichment of the diet is achieved, an oxidation study can be performed within 8 h, as shown by Elango et al (5). It was shown that long-term adaptation to a specific amino acid-deficient diet does not result in changes of other amino acids in adults (14) but can decrease oxidation of the test amino acid, indicating a decrease in catabolism to maintain the body's equilibrium (15,16). Because these studies used the direct amino acid oxidation method, which is proposed to produce low oxidation rates in response to lower intakes of the test amino acid, these results are not comparable with our results using the IAAO method, in which deficient intakes are proposed to give high oxidation rates.…”
Section: Articlesmentioning
confidence: 99%
“…In a response to this restriction arginine homeostasis is maintained. Results indicate a reduced rate of arginine oxidation with maintenance of endogenous arginine synthesis, which occurs at a rate of about onethird of the dietary intake level (Tharakan et al, 2008). However, the present diet contained alanine and serine that presumably serve as adequate sources of α-amino N. It is to be considered that these results can be applied only to healthy subjects and with nutritional balance, whereas a source of dietary arginine is required in severely stressed patients and so in this case arginine is a conditionally indispensable amino acid (Yu et al, 2001).…”
Section: Attenuation Of Argininosuccinate Lyasementioning
confidence: 96%